Impulsivity and tonality of noise due to commercial vehicles transit on rumble strips - 610446 Wan Mohammad Asyraf Norudin 1994- , author; Zaiton Haron, supervisor 277908; Khairulzan Yahya, supervisor 458383; Nadirah Darus, 1990- supervisor 554498; Fakulti Kejuruteraan Awam 8022 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2017